PRESCHOOL EDUCATION QUALITY ASSESSMENT, MONITORING AND INTERNATIONAL COOPERATION (Multidisciplinary Journal of Science and Technology, 2026)
This scientific article analyzes the theoretical foundations of assessing the quality of preschool education, the importance of monitoring systems, and the role of international cooperation in improving education quality. The reforms implemented in the preschool education system of Uzbekistan, modern monitoring methods, and mechanisms for quality control are examined.